Parent-to-parent advice before the birth of a stillborn baby - Kremkow, Jennifer M. D.; Lamberson, Jessica (Frontiers in Psychiatry, 2025)
IntroductionStillbirth is a traumatic experience for parents who expect to welcome a living baby into their family, but find out during their pregnancy or during birth that their baby has died. Some stillbirth literature focuses on the lived experiences of parents such as memory making activities; however, few articles offer peer advice to newly bereaved parents.MethodsA self-administered online survey was utilized to collect parent-to-parent advice for newly bereaved parents. After data cleaning, 194 parent participant responses to the question “What should new loss parents know before the birth of their stillborn baby?” remained. Content analysis was used to analyze the responses.ResultsContent analysis generated four main clusters respondents felt newly bereaved parents should know before the birth of their stillborn baby: (1) the birthing process, (2) the decisions about their baby, (3) memory making activities, and (4) the emotions before and after their baby’s birth.DiscussionThis manuscript builds on limited previous literature by focusing on advice parents who experienced the birth of a stillborn baby would give to new loss parents experiencing stillbirth before going to the hospital. Advice from parent participants may be helpful for newly bereaved parents, healthcare and mental health providers, and organizations or non-profits supporting newly bereaved families.